Vertical co-current two-phase flow regime identification using fuzzy C-means clustering algorithm and ReliefF attribute weighting technique - Pan, Liang-ming; Zhang, Muhao; Ju, Peng; He, Hui; Ishii, Mamoru (International journal of heat and mass transfer, 2016)
•Air–water two-phase upward and downward flow experiments are conducted in 25.4mm round tube.•ReliefF-FCM is proposed to identify the flow regime objectively.•The flow regime maps based on the present identification results are obtained for both upward and downward flow.•Discussions of L/D and entrance effects are conducted. In order to develop the flow regime identification map by objective method, air–water two-phase upward and downward flow experiments were conducted in a tubular test section with the inside diameter of 2.54cm. This study focused on (1) a new objective flow regime identification method based on the fuzzy C-means (FCM) clustering algorithm and ReliefF attribute weighting algorithm, (2) the construction of the objective flow regime map on the basis of the identification results of the proposed objective method and (3) the discussion of entrance and L/D effects for co-current upward and downward two-phase flow. The ReliefF-FCM method successfully identified flow regime and the flow regime maps obtained by this method showed the same trends as the maps of Mishima–Ishii and Usui for upward and downward flow, respectively. Furthermore, in comparing with the previous objective flow regime identification methods, the remarkable advantage of the method represented in the paper was discussed. By comparing the flow regime maps at different positions of test section, the entrance and L/D effects on the flow regime transition were also considered.